2021
DOI: 10.3390/vaccines9070800
|View full text |Cite
|
Sign up to set email alerts
|

Mutation E48K in PB1 Polymerase Subunit Improves Stability of a Candidate Live Attenuated Influenza B Virus Vaccine

Abstract: Influenza B virus (IBV) is a major respiratory pathogen of humans, particularly in the elderly and children, and vaccines are the most effective way to control it. In previous work, incorporation of two mutations (E580G, S660A) along with the addition of an HA epitope tag in the PB1 segment of B/Brisbane/60/2008 (B/Bris) resulted in an attenuated strain that was safe and effective as a live attenuated vaccine. A third attempted mutation (K391E) in PB1 was not always stable. Interestingly, viruses that maintain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The humoral responses induced by the rearranged virus vaccines were analyzed utilizing serum samples obtained at 19 days post-boost (19 dpb) from a subset of 4 mice/group (2 males, 2 females, except in the FluB-RAM group with 1 male and 2 female serum samples). Please note that we included HI data from FluB att as it was part of the same study, although it was reported elsewhere [39]; these data were included for comparison purposes. Boost vaccination led to HI titers above 40, the predictive limit of protection (Figure 2C) with either rearranged virus.…”
Section: Qualitative Differences In Humoral Responses Among Different Vaccine Groupsmentioning
confidence: 99%
“…The humoral responses induced by the rearranged virus vaccines were analyzed utilizing serum samples obtained at 19 days post-boost (19 dpb) from a subset of 4 mice/group (2 males, 2 females, except in the FluB-RAM group with 1 male and 2 female serum samples). Please note that we included HI data from FluB att as it was part of the same study, although it was reported elsewhere [39]; these data were included for comparison purposes. Boost vaccination led to HI titers above 40, the predictive limit of protection (Figure 2C) with either rearranged virus.…”
Section: Qualitative Differences In Humoral Responses Among Different Vaccine Groupsmentioning
confidence: 99%
“…Lethality of Phu/13 and FL/4/06 in Mice Prior to Mouse-Adapting Influenza viruses do not typically cause disease in mice. However, lethal challenge strains of influenza are often optimal for vaccine and therapeutics studies [26,29,[32][33][34]. Therefore, mouse-adapting is used to produce a disease model for use in laboratory studies [23,26].…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, the inability to naturally cause infections in many mouse strains has led to difficulty of developing easily accessible small animal disease models for IBV vaccine and therapeutic research. The process of mouse-adapting IBV has been used to define in vivo pathogenic determinants [24][25][26] and for development of lethal strains for use in vaccine and therapeutics studies [32][33][34]36]. However, performing mouse-adapting series can be costly and may not produce consistent or repeatable results.…”
Section: Discussionmentioning
confidence: 99%
“…The PB1 plasmids containing the re-arranged M (PB1BM2) and re-arranged NS (PB1BNS2) and the M and NS plasmids encoding early stops codons have been previously described 18 . The PB1 plasmid containing the temperature sensitive mutations and C-terminal HA tag (pDP-PB1att) was previously described 21,29 . The plasmid pDP_B/Bris-PB1_Nluc (B/Bris) was produced carrying a chimeric PB1 gene segment from B/Brisbane/60/2008 (B/Bris) WT with an in-frame C-terminal nanoluciferase ORF (Nluc) between the C-terminal end of the PB1 ORF and the 3'UTR.…”
Section: Recombinant Plasmidsmentioning
confidence: 99%